Impact of left anterior descending lesion location on midterm outcomes in patients undergoing left internal mammary artery grafting: a five-year cohort study integrating quantitative flow ratio assessment - Sun, Ziang; Wu, Yuhui; Jiang, Rui; Chen, Zeyu; Wang, Tianyu; Yan, Wenlong; Yang, Sumin (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe prognostic value of coronary artery bypass grafting (CABG) may be suboptimal when guided solely by anatomical stenosis severity. Quantitative flow ratio (QFR), a computational angiography-derived hemodynamic assessment tool, offers functional insights; however, its prognostic interplay with lesion localization [proximal vs. mid-to-distal left anterior descending artery (LAD)] remains unclear. This study evaluates the impact of QFR-guided revascularization, stratified by LAD lesion location, on midterm clinical outcomes.MethodsA retrospective cohort of 481 patients undergoing left internal mammary artery (LIMA) to LAD grafting (2019–2023) was analyzed. Lesions were classified as proximal (Site 1) or mid-to-distal (Site 2) LAD and stratified by QFR thresholds (High: ≥0.80; Low: <0.80). The primary endpoint was 5-year major adverse cardiovascular and cerebrovascular events (MACCEs), assessed using Kaplan–Meier survival analysis and Cox regression.ResultsHigh QFR patients (n = 139) exhibited lower diabetes (28.1% vs. 40.6%, p = 0.013), smoking rates (27.3% vs. 38.6%, p = 0.025), and 3-vessel disease (48.9% vs. 74.6%, p < 0.0001) compared to low QFR (n = 342). Proximal lesions with high QFR had markedly higher MACCEs risk (HR = 1.91, 95% CI: 1.18–3.10; Log-rank P = 0.0075), whereas mid-to-distal lesions showed no QFR-driven prognostic differences (p = 0.46). Lesion location alone did not independently influence survival (Log-rank P = 0.8).ConclusionQFR-guided risk stratification is most prognostically impactful for proximal LAD lesions, where hemodynamic significance plays a critical role in clinical outcomes. In contrast, mid-to-distal lesions exhibit limited QFR utility, emphasizing anatomical-functional synergy in CABG planning. Despite comparable survival across lesion sites, proximal low QFR lesions warrant intensified surveillance.